“Pô, tô vivo, véio!”: história de vida e sexualidade de pessoas com deficiências físicas - Oliveira, Everton Luiz de (2016)
In this study we aimed to investigate, beside people with physical disabilities, how they express their sexuality from their life stories and their impairment/disabled bodies. The Life History, being defined as one of the theoretical contributions, made it possible to establish a channel through which disabled people could relive facts, experiences and events related to sexuality, identifying ways, glances, pleasures and printed sensibilities through injured, amputated and disabled bodies. Other theoretical contributions, from the anthropological social field, especially the critical studies of disability (Disability Studies), substantiated the ways and debates in the intersection with the sexuality field. Hence, we defined the Collective Subject Discourse (DSC) as the study method, especially to encompass analysis techniques that allow gathering ideas, senses and thoughts of the same social group, projecting a single collective discourse in the light of various themes. The sample was composed of three people with physical disabilities, heterosexual men, members of an institution that provides services to people with disabilities, in a city in the interior of São Paulo state. Data collection took place through open interviews (recorded audio), without pre-established scripts and have been developed until to reach a saturation point (exhaust affairs). The meetings took place without delimitation of time or amount, varying according each participant. All interviews were transcribed, and the analysis took place based on techniques used in DSC, using their methodological approaches. The composition of the DSC enabled understanding the sexuality of people with physical disabilities as it is still regulated by policy and biomedical processes, which make pathological not only people with disabilities, but anyone who shows attraction, erotic and sexual desire by people with injured, amputated or disabled bodies. There is an urgent need to admit new aesthetic, sexual and political horizons for the physically disability, projecting the injured, amputated and disabled body as beautiful, desirable, sexy, attractive and, undeniably, delicious. Only from that aesthetic reconfiguration of disability, each and every disabled person will be accepted as a sexual and sexualized person.